A RESEARCH ON THE AVAILABILITY OF RISK CAPITAL IN RESOLVING THE MARKETING AND FINANCE PROBLEMS OF SMALL AND MEDIUM-SCALE ENTERPRISES (SMEs) (International Journal of Innovative Technologies in Economy, 2024)
Small and medium-sized enterprises (SMEs) play a vital role in many economies, serving as a source of technological innovation and a foundation for larger enterprises. However, SMEs often face significant challenges in the areas of marketing and finance. This study aims to investigate the potential of venture capital in addressing these issues and facilitating the growth and development of SMEs. Methods: A comprehensive survey was conducted among SMEs in the computer, machinery, equipment, textile, and related product manufacturing sectors in the Izmir and Istanbul provinces of Turkey. The target population consisted of 250 SMEs, with a goal of reaching a representative sample of 100 enterprises. Data was collected through face-to-face interviews and mailed questionnaires, and analyzed using non-parametric tests in SPSS. Results: The findings reveal that SMEs face numerous marketing challenges, including difficulties in market penetration, intense competition, unfair trade practices, and restrictive economic policies. Financial constraints were also prominent, with SMEs struggling to secure loans due to high collateral requirements, limited credit opportunities, and bureaucratic obstacles. Notably, while nearly half of the respondents were aware of venture capital as a financing tool, only 6% had actually utilized it, primarily due to a lack of detailed knowledge about the mechanism. Discussion: The study underscores the critical need for alternative financing options, such as venture capital, to support the growth and competitiveness of SMEs. Policymakers and financial institutions should prioritize initiatives to increase awareness and accessibility of venture capital, while also addressing the broader regulatory and infrastructural barriers faced by SMEs. Future research should explore the specific factors influencing venture capital adoption and its impact on SME performance across diverse contexts.